BSC-Based Performance Evaluation Model for Securities Industry and Its Application. (14th July 2022) - Yuan, Ling; Sun, Shan-Hui; Cai, Zheng-Qun
Abstract : In the study on China's securities industry, the securities industry is divided into four types: investment in securities, securities brokerage, securities consulting, and securities underwriting and asset management. In this paper, a performance evaluation index system for the securities industry is established by using the balanced scorecard method. Based on the analytic hierarchy process, entropy weight method, and improved entropy weight method, we propose the traditional integrated weighting method and improved integrated weighting method, thus arriving at four different index weight systems. Finally, we work out the comprehensive scores of four types of securities companies under the four index weight systems, analyze the actual situation of China's securities industry by comparing the scores and rankings of securities companies under the four index weight systems, and then put forward specific suggestions.